Etika Lingkungan dalam Pembelajaran IPA Berbasis Ekowisata - Muh. Zaini Hasanul Muttaqin; Muhammad Sarjan; Joni Rokhmat; Agus Muliadi; Asrorul Azizi; Bachtiar Ardiansyah; Hamidi Hamidi; Iswari Pauzi; Muhammad Yamin; Mulia Rasyidi; Rindu Rahmatiah; Sudirman Sudirman; Yusran Khery (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
This article aims to examine the concept of environmental ethics in ecotourism-based science learning. In conventional education, the educational process only focuses on knowledge (cognitive) while the attitude aspect only gets a very small portion. Environmental ethics in ecotourism-based science learning is expected to integrate various science concepts and contextual science learning objectives with the ecotourism concept, so that the formation of environmental care characters in students and the implementation of ESD can be realized optimally. This research uses literature study method. The data used in this study were sourced from scientific articles (national and international, science textbooks (SD, SMP and SMK), reference books, and literature reviews related to the concepts studied. Based on the above reviews, it can be concluded that the concept of environmental ethics that mostly presented in science learning materials at all levels of primary and secondary education dominated by anthropocentrism theory, while the concept of ecotourism is mostly presented at the vocational level with the Tourism Expertise Program.